Tradisi Menyiapkan Hidangan Ketika Orang Meninggal Dunia (Kajian Living Hadis Terhadap Tradisi Di Masyarakat Desa Paya Ketenggar Dan Desa Bagok Panah Sa) - Maisyarah, Sindi (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
Tradition is a habit that has been continuosly carried out from the time of our ansectors to the present. In Indonesia there are very diverse traditions carried out by Indonesian people. The tradition preparing food when people die in Aceh is very different in its implementation. Preparing dishes namely preparing food in the form of staple foods or snacks that will be given to people in need. This tradition is out after the death of someone. There is a lot of debate among the people about this tradition. Some argue that it was the neighbors who were advised to prepare food and give it to the deceased’s family. There are also those who argue that the deceased’s family may prepare dishes and give them to the guests who attend. As implemented by Paya Ketenggar and Bagok Panah Sa arrow village which differ in their application so that there are pros and cons. The ith type of research used is field research. The method used is qualitative a sociological approach.  Collection of data obtained from the results of interviews, observation and documentation.